O mau cheiro sobre as bases da sustentação psíquica - Bonomi, Tomás Moraes Abreu (2015)
The present work, inserted in the fundamental psychopathology field of study, is based on a clinical situation. The patient demands analysis because all her love relationships failed which caused intense suffering. After a few sessions the patient says she knows why her relationships come to an end: She stinks. The stench becomes a recurring theme during her analysis both in her speech as in her dreams, memories, fantasies, hallucinations and also in the transfer with the analyst. A clinical hypothesis is formulated in the terms of the stench being a defense mechanism. As theoretical foundation the following psychoanalytical concepts will be used: symptom, narcissism, defense mechanism, hallucinations, anxiety, femininity among others. Finally, are mapped different functions of the stench in the psychic dynamism and therefore discusses his role as psychic support base